1977
DOI: 10.1002/app.1977.070210717
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and molecular weight calculations in GPC using a new practical method for dispersion correction—GPCV2

Abstract: SynopsisThe method of Balke, Hamielec, LeClair, and Pearce for GPC calibration and molecular weight computation is reviewed and evaluated. A new method, called GPCVB, is proposed which uses the single broad molecular weight distribution (MWD) standard for calibration developed by those workers, but which also incorporates the chromatographic dispersion u to make the method more accurate in genera! use. Equations are presented for computing the relationship between actual MW and retention volume V R under the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…Since peak spreading is not accounted for in this method, an ''effective'' rather than the true calibration is obtained. Improved versions of this procedure, which do account for peak spreading, have been proposed by Yau et al [27]. This method can be extended to a nonlinear calibration curve by using more than one standard with independently determined molecular weight averages.…”
Section: Calibration With Broad Standardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since peak spreading is not accounted for in this method, an ''effective'' rather than the true calibration is obtained. Improved versions of this procedure, which do account for peak spreading, have been proposed by Yau et al [27]. This method can be extended to a nonlinear calibration curve by using more than one standard with independently determined molecular weight averages.…”
Section: Calibration With Broad Standardsmentioning
confidence: 99%
“…Recently, Jackson [84] performed a computer simulation in order to evaluate the ''effective volume shift'' method for axial dispersion corrections in multidetector size exclusion chromatography. He found that although the method gave satisfactory results for SEC with an LS detector, it failed for SEC with an intrinsic viscosity detector, and he concluded that in this case, the conventional approach [27] outlined above gives more accurate results. Striegel [85] tried to evaluate the effect of axial diffusion on SEC band broadening by using a stop-flow technique.…”
Section: Peak Spreadingmentioning
confidence: 99%
“…The linear calibration methods using broad polymer standards are discussed here beginning with the original form developed by Hamielec [21], followed by the discussions of the improved versions (GPCV2, GPCV3) of Yau et al [22,26] and others [23][24][25].…”
Section: Linear Calibration Methodsmentioning
confidence: 99%
“…The true values of M w and M n of a polymer sample for linear calibration (Equation 4.5) can be written as [8][9][10][11] (M n ) true = 1 The true values of M w and M n of a polymer sample for linear calibration (Equation 4.5) can be written as [8][9][10][11] (M n ) true = 1…”
Section: Molar Mass Accuracy Criterionmentioning
confidence: 99%
“…The true and experimental molar mass averages can be related to each other directly by a single correction factor X [8][9][10][11]:…”
Section: Molar Mass Accuracy Criterionmentioning
confidence: 99%